Penerapan Aplikasi Absensi Online untuk Mempermudah Pencatatan Kehadiran di JESSEDREAMCO - Arrohman, Muhammad Rizki; Setiawan, Arif (Universitas Pahlawan Tuanku Tambusai, 2026)
Employee attendance management is a vital component in human resource administration. The Packaging and Marketing Unit of JesseDreamCo lacked any structured attendance recording system, resulting in the absence of credible data for discipline monitoring and performance evaluation. This Community Service (PkM) activity aims to establish an accurate and efficient attendance system from scratch. The method employed is the System Development Life Cycle (SDLC) focusing on Diffusion of Science and Technology (Ipteks), which includes needs analysis, design of a mobile-based attendance application utilizing QR Code technology and Location Based System (LBS). This was followed by intensive Training and assistance. The results demonstrate success in creating an administrative structure where none existed before. The new system facilitates validated attendance records and quantitatively achieved a report recapitulation time efficiency of over 90%. In conclusion, initiating attendance digitalization with validation features is fundamental to establish internal control and enhance employee discipline in SMEs transitioning toward structured administration.